Epidemiology of digestive bleeding - Ichiyanagui Rodríguez, Carlos Enrique (2024)
Gastrointestinal bleeding is a common clinical entity and the main gastroenterological emergency. Since 1994 the Digestive Bleeding Unit, Hospital Rebagliati has acquired great experience in this field. 83% are upper GI bleedings and 17% lower GI bleedings, 63% are male and 37% female. Two thirds are older than 60. The main upper GI diagnoses are: duodenal ulcer (24,5%), gastric ulcer (19,8%) and gastroesophageal varices (15%). The main lower GI diagnosis is colon diverticulosis. The mortality rate in a specialized unit like ours is as low as 3% and the main factors involved are: amount of bleeding, liver cirrhosis, presence of hematemesis.